ERP Sistem Informasi Inventaris Perangkat Keras dan Peripheral Berbasis Enterprise Resource Planning (ERP) - Fauzi Nurfariyanto; Nurmalasari Nurmalasari (Computer Science (CO-SCIENCE), 2022)
The development of information today encourages an increase in effective and efficient work styles. One of the business needs in providing information system tools is technology-based information. When a computerized system shows higher reliability. But at PT. Limawira Wisesa in conducting hardware data collection has not been computerized, such as recording specifications still using Microsoft Excel so that data collection feels inefficient and can cause errors and errors in recording specifications. Based on these problems, a hardware, and peripheral inventory information system was built to make it easier to search for data quickly and precisely and provide convenience to related staff in managing hardware and peripheral specification data. The information system begins with system requirements analysis, system design, program code, and program testing, and is built according to the waterfall method. The staff involved in managing hardware specification data can access the admin user. The information system is built based on enterprise resource planning, namely the Inventory Module so that the system is integrated with other systems at PT. Limawira Wisesa.